2009
DOI: 10.1016/j.jmb.2008.12.061
|View full text |Cite
|
Sign up to set email alerts
|

The Folding Free-Energy Surface of HIV-1 Protease: Insights into the Thermodynamic Basis for Resistance to Inhibitors

Abstract: Spontaneous mutations at numerous sites distant from the active site of HIV-1 protease enable resistance to inhibitors while retaining enzymatic activity. As a benchmark for probing the effects of these mutations on the conformational adaptability of this dimeric β-barrel protein, the folding free energy surface of a pseudo wild-type variant, HIV-PR*, was determined by a combination of equilibrium and kinetic experiments on the urea-induced unfolding/refolding reactions. The equilibrium unfolding reaction was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 54 publications
3
32
1
Order By: Relevance
“…Each 99-residue monomer contributes a catalytically essential aspartic acid (Asp25) to the enzyme active site, which contains a conserved triad sequence, Asp-Thr-Gly, and resembles that of other aspartyl proteases [73]. The folding of this enzyme is a three-state process in which two monomers first fold independently and then dock in the dimer native state [216][217][218].…”
Section: Intrinsic Disorder In Non-structural Proteinsmentioning
confidence: 99%
“…Each 99-residue monomer contributes a catalytically essential aspartic acid (Asp25) to the enzyme active site, which contains a conserved triad sequence, Asp-Thr-Gly, and resembles that of other aspartyl proteases [73]. The folding of this enzyme is a three-state process in which two monomers first fold independently and then dock in the dimer native state [216][217][218].…”
Section: Intrinsic Disorder In Non-structural Proteinsmentioning
confidence: 99%
“…Unfolding of HIV-1 PR monomer facilitated by denaturing agents was studied by Noel et al 10 who showed that certain mutations in the protease sequence increase its tendency to unfold. Moleculardynamics simulations were carried out in order to explain the mechanism of monomer folding and characterize its intermediates 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 PT is a homodimer with 99 residues per subunit (Fig. 9), and each subunit is composed of nine -strands and one -helix (Noel et al, 2009). -Strands 2 to 8 are involved in the formation of a jelly-roll -barrel topology within each subunit.…”
Section: Hiv Protease Inhibitors 241 the Structure Of Hiv Proteasementioning
confidence: 99%
“…-Strands 2 to 8 are involved in the formation of a jelly-roll -barrel topology within each subunit. The dimeric interface contains an antiparallel -sheet formed by the interdigitation of the N-and Cterminal -strands in each subunit and by an interlocking and balanced pair of threonines, Thr26, in the active site (Noel et al, 2009). The active site-needing proteolysis is embed in the flap tips and crossing the subunit interface.…”
Section: Hiv Protease Inhibitors 241 the Structure Of Hiv Proteasementioning
confidence: 99%